Emotional Intelligence and Work Performance in Young and Middle Adulthood - Ms. Sheeba Jacintha; Dr. Rema M K (International Journal of Indian Psychȯlogy, 2022)
Present study aimed to examine the influence of emotional intelligence on work performance in working individuals. The study also focused on the age wise comparison of Emotional intelligence and work performance. Sample consists of 232 full-time working professionals from various fields selected using purposive sampling method. Tools used for the present study are Emotional Intelligence Self-Assessment Tool developed by Emily. A. Sterett (2014) and Individual Work Performance Questionnaire (IWPQ) developed by Linda Koopmans (2014). Results were analysed using descriptive statistics, and Pearson correlation. The findings showed that task performance and contextual performance have a positive relationship with emotional intelligence, whereas, counterproductive work behaviour is negatively correlated to emotional intelligence. The results also showed that there is a significant difference in emotional intelligence of the two age groups, however, there is no significant difference in work performance of the two age groups.